The synergistic effects of Lactobacillus acidophillus ROO52 and Lactobacillus bulgaricus LB-12 bacteriocins against E.coli O157 :H7 in milk - khudhir, Zina Saab (The Iraqi Journal of Veterinary Medicine, 2014)
The aims of this study to evaluate the antibacterial potential of standard strains (Lactobacillus acidophilus ROO52 and Lactobacillus bulgaricus LB-12) that produce bacteriocins against E.coli O157:H7 in raw milk. Thirty raw milk samples randomly were collected weekly different markets of Baghdad city in order to investigate the prevalence of E.coli O157:H7 in milk. The prevalence of E.coli O157:H7 in raw milk samples was 6 out 30 (20%) by using the modern chromogenic media with serological latex agglutination test kit. The average diameter of the inhibition zone of crude bacteriocin against E .coli O157:H7 by using combination of 1:1 (v/v) of the Lactobacillus acidophillus ROO52 and Lactobacillus bulgaricus LB-12was (14mm) ,while that produced by bacteriocins of Lactobacillus acidophillus ROO52 and Lactobacillus bulgaricus LB-12 independently were 16 and 12mm respectively .L. delbrucekii ssp bulgaricus showed significantly (P<0.05) low antimicrobial effect against E.coli O157 :H7 .While the strongest antimicrobial effect was shown by Lactobacillus acidophilus ROO52. The bacteriocins of the reference strains used in this study did not result in an increase in inhibition when used in combination of 1:1 (v/v).